Reliability of Family History Report among Relatives of Aggressive Periodontitis Patients (Mustansiria Dental Journal, 2018)
To assess the periodontal status among relatives of aggressive periodontitis (AgP) patients and to evaluate the reliability of the family history report as provided by the proband.Fifty AgP patients were identified during 2005/2006 as fulfilling the criteria to be diagnosed as AgP as outlined in the 1999 international classification system for periodontal disease. These subjects met the clinical criteria for either localized or generalized AgP.It was considered that AgP patients should be informed of the genetic nature of their condition and that other blood relatives could be at risk. The results would suggest that the screening of relatives with a positive family history could be justified as a standard procedure, but negative family history reports are unlikely to yield significant numbers of affected relatives and may not be a justifiable use of scarce resources.The report given by the proband was considered reliable. If the report was positive, it was followed by diagnosis of periodontitis in 73% of the cases, while if it was negative, periodontitis was absent in 66% of the cases.